2018
DOI: 10.1140/epjc/s10052-018-5582-x
|View full text |Cite
|
Sign up to set email alerts
|

de Sitter relativity in static charts

Abstract: The relative geodesic motion in static (and spherically symmetric) local charts on the (1 + 3)-dimensional de Sitter spacetimes is studied in terms of conserved quantities. The Lorentzian isometries are derived, relating the coordinates of the local chart of a fixed observer with the coordinates of a mobile chart considered as the rest frame of a massive particle freely moving on a timelike geodesic. The time dilation and Lorentz contraction are discussed pointing out some notable features of the de Sitter rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…However, these propagators, depending explicitely on the Heaviside step functions, cannot be used in calculating Feynman diagrams without an integral rep. which should encapsulate the effect of these functions. This is why we proposed recently a new type of integral rep. which takes over the effect of the step functions but is different from the Fourier integrals used in special relativity [13]. Thus we completed the theory of the free Dirac fermions on the de Sitter expanding universe [14,15,16] with the integral rep. of the Feynman propagators we need for calculating physical effects in our de Sitter quantum electrodynamics (QED) in Coulomb gauge [17] using perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these propagators, depending explicitely on the Heaviside step functions, cannot be used in calculating Feynman diagrams without an integral rep. which should encapsulate the effect of these functions. This is why we proposed recently a new type of integral rep. which takes over the effect of the step functions but is different from the Fourier integrals used in special relativity [13]. Thus we completed the theory of the free Dirac fermions on the de Sitter expanding universe [14,15,16] with the integral rep. of the Feynman propagators we need for calculating physical effects in our de Sitter quantum electrodynamics (QED) in Coulomb gauge [17] using perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…In our investigations we observed that on dS and AdS spacetimes there are special static charts [8,9] with Cartesian coordinates in which the geodesic equations can be expressed simply, in terms of conserved quantities, without using explicitely initial conditions [4,5,7]. These results can be generalized easily to any dimensions by using the same type of static charts.…”
Section: Introductionmentioning
confidence: 61%
“…Finally we note that here we respected up to signs our previous definitions given in the cases of d = 3 for the dS [3,4] and AdS [6,7] manifolds. Therefore, we find similar flat limits (for ω → 0) that read…”
Section: Particles On Hyperbolic Spectimesmentioning
confidence: 94%
See 2 more Smart Citations